A green approach to adaptive cultivation of Chlorella sorokiniana in oilfield hypersaline wastewater for sustainable biomass production, nutrient removal, and bioenergy potential - Mohammed Omar Faruque; Mohammad Mozahar Hossain; Shaikh Abdur Razzak (Green Technologies and Sustainability)
Microalgae, particularly Chlorella sorokiniana (C. sorokiniana), present a promising avenue for sustainable biomass production due to their ability to accumulate valuable macromolecules under diverse environmental conditions. This study investigates the progressive adaptation and characterization of C. sorokiniana in synthetic oilfield hypersaline brine (HSB), a byproduct of oil extraction that poses significant environmental challenges due to high salinity. The microalgae were cultivated in photobioreactors containing varying concentrations of HSB (0% to 60%) supplemented with synthetic municipal wastewater (SMW) for essential nutrients. The maximum biomass output ranged from 237 mg L−1 to 1373 mg L−1, with the highest concentration achieved at 30% HSB loading. Significant nutrient removal was observed, with a maximum of 89.1% nitrogen and 98.48% phosphorus removal at specific HSB concentrations. Proximate and ultimate analyses revealed that C. sorokiniana biomass contained higher carbohydrate content (25% to 62.87%) compared to protein (15.37% to 19.81%) and lipid (3.7% to 30.94%). Notably, the biomass exhibited a higher heating value of 22.84 MJ/kg, surpassing that of lignocellulosic biomass, indicating its potential as a sustainable bioenergy source. The novelty of this study lies in its pioneering exploration of C. sorokiniana’s adaptation to synthetic HSB, coupled with the innovative integration of HSB and SMW, offering a sustainable strategy for biomass production while addressing waste management challenges.